2020
DOI: 10.9734/ijecc/2020/v10i1030248
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Pre Released Rice (Oryza sativa L.) Genotypes under Different Sowing Windows in Rabi Season

Abstract: The aim of this study was to investigate the effect of different sowing dates on growth and yield potential of pre released rice genotypes under irrigated conditions of Northern Telangana zone. The field experiments were carried out during two consecutive rabi seasons of 2018-19 and 2019-20, on clay soils of agricultural research station, Kunaram, Telangana state, India. The experiment was laid out in strip plot design with three replications. The treatments comprised of three sowing dates i.e. 20th November, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Similar findings were reported by Bindu and Bhanumurthy [7]. These results align with the research conducted by Anil and Siddi [8] and Bindu [9], who reported that plant height is influenced by genotypes, various management factors and the environment. The increased plant height observed in delayed sowings in the season could be attributed to greater exposure to solar radiation and heightened photosynthetic activity.…”
Section: Plant Heightsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings were reported by Bindu and Bhanumurthy [7]. These results align with the research conducted by Anil and Siddi [8] and Bindu [9], who reported that plant height is influenced by genotypes, various management factors and the environment. The increased plant height observed in delayed sowings in the season could be attributed to greater exposure to solar radiation and heightened photosynthetic activity.…”
Section: Plant Heightsupporting
confidence: 92%
“…It might be due to the genetic character of the variety and higher photosynthetic efficiency. These results are similar to those obtained by Anil and Siddi [8], Nizamani et al [11] and Suleiman et al [12] who observed that plant height differed significantly among the varieties.…”
Section: Plant Heightsupporting
confidence: 92%
“…Lower values of grain yield were found in M 3 (Chintu).The superiority of Telangana sona and Jagtial rice 1 might resulted from its better growth character i.e., dry matter accumulation.These results are in accordance with Bindu [19]. Among different sowing and harvesting dates, S 5 (Delay sowing by 30 days (December 15) and harvesting at physiological maturity) shown significantly higher grain yield over all other treatments followed by S 6 (Delay sowing by 30 days (December 15) and harvesting at 7 days after physiological maturity), which was on par with S 1 (Normal sowing time (November 15) and harvesting at physiological maturity )and S 3 (Delay sowing by 15 days (November 30) and harvesting at physiological maturity).The lower values of grain yield were found in S 2 (Normal sowing time (November 15) and harvesting at 7 days after physiological varieties sowing and harvesting dates maturity).The increased yield might be due to higher dry matter accumulation associated with favorable temperature in delayed sowing responsible for more growth and development, resulting in more storage of photosynthates in the grain during rabi conditions.These findings are similar to Bindu [19].These results are in accordance with Anil and Siddi [9] and Chendge et al [20].The interaction effect was found nonsignificant for grain yield of rice crop among the varieties and different sowing and harvesting dates.…”
Section: Grain Yieldsupporting
confidence: 91%
“…Though some studies were carried out regarding performance of long slender rice varieties in rabi season. pertaining to yield Anil and Siddi [9], no research studies were conducted with market demand fine grain rice varieties especially under delayed sowings/harvestings, which is a common problem in most of the farmers fields. By considering all the above facts, the following work was put forth.…”
Section: Introductionmentioning
confidence: 99%
“…The significant and higher grain yield was observed with the variety Chakhao Poireiton might be due to higher number of effective tillers attributed to higher affinity of this variety and yield contributes associate with favourable weather condition followed by differential ability of cultivars and photoassimilate, which resulted in the higher grain yield. Similar result was reported by Anil and Siddi [32]. Further significantly higher grain yield was observed with the application of nitrogen (80 kg/ha) might due to the availability more water enhanced nutrient availability which improved nitrogen and other macro and microelements absorption enhancing the production.…”
Section: Grain Yield (T/ha)supporting
confidence: 86%